2009
DOI: 10.1111/j.1365-2109.2009.02271.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the temporal effects of spawning season and maternal and paternal differences on egg quality in Atlantic codGadus morhuaL. broodstock

Abstract: A better understanding of the parameters a¡ecting egg quality and larval survival is of importance for continued development of cod broodstock and e⁄cient husbandry practices. Decision tree analysis (DTA) was applied to analyse 3 years of egg quality data in an e¡ort to extract the most important variables (i.e. predictors) in explaining di¡erences in egg quality. The e¡ect of three predictors (spawning time, maternal and paternal di¡erences) has been studied on early cleavage pattern parameters, egg diameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…This was also observed during one year with Lake Oahe Chinook Salmon eggs [1]. However, studies with Chinook Salmon and other Salmonids have found no correlation between the egg size and survival [1,50,51].…”
Section: Discussionmentioning
confidence: 77%
“…This was also observed during one year with Lake Oahe Chinook Salmon eggs [1]. However, studies with Chinook Salmon and other Salmonids have found no correlation between the egg size and survival [1,50,51].…”
Section: Discussionmentioning
confidence: 77%
“…(2009); Hamoutene et al . (2009); and Bobe & Labbé (2010), among others, have questioned and studied blastomere symmetry, but only from a morphological point of view. For this study in S. salar , a morphometrical criterion was used for the first time to evaluate these asymmetries, an approach similar to that considered in Oncorhynchus kisutch by Effer et al .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with the morphological criteria for the evaluation of symmetry of the first blastomeres in fish adopted by several groups (Kjorsvik et al ., 1990; Shield et al ., 1997; Kjorsvik et al ., 2003; Rideout et al ., 2004; Avery & Brown, 2005; Penney et al ., 2006; Moran et al ., 2007; Pavlov & Emel'yanova, 2008; Avery et al ., 2009; Hamoutene et al ., 2009), in this study the symmetry of the embryos of two and four blastomeres was considered to determine the proportions of lengths and width of all of the blastomeres (from the same blastodisc). This approach was an alternative to that considered in S. salar by Effer et al .…”
Section: Discussionmentioning
confidence: 99%